Physiological and biochemical processes in spring barley under separate and integrated application of herbicides and plant growth regulators - Білоножко, В. Я.; Карпенко, В. П.; Полторецький, С. П.; Притуляк, Р. М. (Scientific Progress & Innovations, 2012)
The article summarizes the results of a long term research into the influence of sylphonylurea herbicides (Granstar 75, Caliber 75, Harmony 75), phenoxy-carboxylic acids (2,4-DA 500, Dicopur F 600) and combined preparations (Lintur 70 WG) applied separately and in combination with plant growth regulators (Emistim C, Agat-25K and Agrostimulin) on physiological and biochemical processes in spring barley which predetermine the formation of plantings productivity.